2009
DOI: 10.1177/1941406409349958
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothers’ Involvement in Preschool-Aged Children’s Consumption of Fruits and Vegetables

Abstract: A social-ecological framework suggests that nutrition education programs designed to increase young children's fruit and vegetable consumption should address the influence of immediate and extended family. However, very few nutrition education programs recognize the importance of grandmothers in shaping preschoolaged children's consumption patterns. This study explored the impact of grandmothers on their grandchildren's fruit and vegetable consumption. Specifically, the authors addressed 3 research questions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 23 publications
1
51
0
Order By: Relevance
“…mother, aunt, grandmother) indirectly influenced the participant by having her food and eating habits remain with participant, mainly as result of upbringing, and 2) Mom directly influenced the participant through interactions with the participant's children, her grandchildren. This study reinforces the findings of the literature on intergenerational influences, which indicates a grandmother may influence her grandchildren's food choices in the following ways: by advising the mother on child feeding; providing foods for her grandchildren; and undermining mother's control of her children's food choices [6,22,41]. This analysis provides additional refinement for understanding intergenerational influences on food choice, and specifically how a grandmother may affect her grandchildren's food choices.…”
Section: Discussionsupporting
confidence: 87%
“…mother, aunt, grandmother) indirectly influenced the participant by having her food and eating habits remain with participant, mainly as result of upbringing, and 2) Mom directly influenced the participant through interactions with the participant's children, her grandchildren. This study reinforces the findings of the literature on intergenerational influences, which indicates a grandmother may influence her grandchildren's food choices in the following ways: by advising the mother on child feeding; providing foods for her grandchildren; and undermining mother's control of her children's food choices [6,22,41]. This analysis provides additional refinement for understanding intergenerational influences on food choice, and specifically how a grandmother may affect her grandchildren's food choices.…”
Section: Discussionsupporting
confidence: 87%
“…A total of 483 studies were identified through the search strategy, with 83 full‐text articles retrieved, of which 16 studies met the inclusion criteria and were included in the review (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…For example, a UK-based study found that grandmothers provided a generally healthy selection of foods to their young grandchildren; however, they were more likely than the children's parents to use feeding practices considered maladaptive, such as regulating the children's emotions through the provision of food (Farrow, 2014), a practice that has been linked to eating without feeling hunger (Baughcum et al, 1998; Blissett et al, 2010). In contrast, a study among US families found that although mothers and grandmothers similarly endorsed feeding fruits and vegetables to young children, compared to the grandmothers, the mothers consumed fewer vegetable servings per day, and were less likely to serve fruits for dinner (Speirs et al, 2009). Adding to the complexity of this landscape, other studies found that those grandparents who spend more time caring for their grandchildren endorse parental feeding practices (Farrow, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, the results have been complex, and at times contradictory (Farrow, 2014; Pulgarón et al, 2013; Speirs et al, 2009). For example, a UK-based study found that grandmothers provided a generally healthy selection of foods to their young grandchildren; however, they were more likely than the children's parents to use feeding practices considered maladaptive, such as regulating the children's emotions through the provision of food (Farrow, 2014), a practice that has been linked to eating without feeling hunger (Baughcum et al, 1998; Blissett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%